Involvement of Cerebral Nervous System Areas and Cytokines on Antihyperalgesic and Anti‐Inflammatory Activities of Kielmeyera rugosa Choisy (Calophyllaceae) in Rodents. (2nd August 2014) - Melo, M.S.; Brito, R.G.; Santos, P.L.; Nogueira, P.C.L.; Moraes, V.R.S.; Matos, M.C.P.; Ferro, J.N.S.; Barreto, E.O.; Lucca Junior, W.; Botelho, M.A.; Quintans Junior, L.J.
<x xml:space="preserve">Abstract</x> Kielmeyera rugosa is a medicinal plant known in Northeastern Brazil as 'pau‐santo', and it is used in the treatment of several tropical diseases such as malaria, schistosomiasis, and leishmaniasis. We evaluated antihyperalgesic and anti‐inflammatory activities of methanol stem extract of K. rugosa (MEKR) in mice. The mechanical hyperalgesia induced by carrageenan and tumor necrosis factor‐alpha (TNF‐α), prostaglandin E2, and dopamine were assessed. We also investigated the anti‐inflammatory effect of MEKR on carrageenan‐induced pleurisy and paw edema. Ninety minutes after the treatment, the animals were submitted to an imunofluorescence for Fos protein. MEKR (100, 200, and 400 mg/kg; p.o.) inhibited the development of mechanical hypernociception and edema. MEKR significantly decreased TNF‐α and interleukin 1β levels in pleural lavage and suppressed the recruitment of leukocytes. MEKR (1, 10, and 100 mg/mL) did not produce cytotoxicity, determined using the methyl‐thiazolyl‐tetrazolium assay in vitro. The locomotor activity was not affected. MEKR activated significantly the bulb olfactory, piriform cortex, and periaqueductal gray of the central nervous system. Our results provide first time evidence to propose that MEKR attenuates mechanical hyperalgesia and inflammation, in part, through an activation of central nervous system areas, mainly the periaqueductal gray and piriform cortex areas. Copyright © 2014 John Wiley & Sons, Ltd.